El fenómeno de la esclavitud en el noroeste hispanorromano a través de los testimonios gráficos - García Martínez, Sonia María (Estudios humanísticos. Geografía, historia y arte, 1999)
In this article, it’s analized the phenomenon of slavery in the North-west of Hispania during the roman period according to the inscriptions of this moment.